PENGARUH TRANSFORMATIONAL, TRANSACTIONAL, AUTOCRATIC, DEMOCRATIC, DELEGATING LEADERSHIP TERHADAP EMPLOYEE PERFORMANCE - KHAUTAL KHAFIDH MUSLIM ALIVENTYNO; IAN NURPATRIA SURYAWAN (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2025)
This research aims to determine the role of effective leadership in influencing the performance of employees at PT. X. The population in this study is the employees of PT. X, totaling 82 employees. Researchers used a questionnaire to collect primary data using a non-probability sampling approach distributed to 75 employees of PT. X. The data analysis method in this study uses Structural Equation Modeling (SEM). The data shows that there is a positive influence of transformational and delegative leadership on the Employee Performance at PT. X. Meanwhile, transactional, autocratic, and democratic leadership styles do not have an influence on the Employee Performance at PT. X. It is recommended that PT. X strengthen the implementation of transformational and delegative leadership styles.